Sweden : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Sweden. (IMF Staff Country Reports; Country Report ;, 2016)
This 2016 Article IV Consultation highlights Sweden's strong economic performance, with real GDP growth heading for about 3.4 percent in 2016 on the heels of an expansion of just over 4 percent in 2015. Employment has increased by 1.5 percent so far in 2016, pushing unemployment down to about 7 percent. Growth is expected to moderate to a still solid 2.4 percent in 2017. The fiscal deficit is expected to be small in 2016, even as migration-related government spending has almost doubled to about 1.4 percent of GDP owing to the surge in refugee inflows in 2015.